تقدير التّبخر- نتح المرجعي الشَّهري في منطقة طرطوس باستخدام الشَّبكة العصبيَّة الصنعيَّة - عمّار, غطفان; الأسعد, علي محمد; عليان, ميس محمد (Latakia University Journal -Engineering Sciences Series, 2019)
يشكّل التبخر- نتح أحد عناصر الدورة الهيدرولوجية، الذي يصعب قياس كمياته الفعلية في الشروط الحقلية، لذلك يجري تقديره اعتماداً على الحسابات بعلاقات تجريبية تعتمد على بيانات عناصر المناخ، وتتضمن تلك التقديرات أخطاء متنوّعة بسبب عمليات التقريب. ويهدف البحث إلى تقدير دقيق لكمية التبخر- نتح المرجعي الشهري في منطقة طرطوس (على الساحل الشرقي للبحر المتوسط)، ويعتمد البحث على تقانة الشبكة العصبية الصنعية، حيث بُني الأنموذج الرياضي باستخدام NN-tool box إحدى أدوات الماتلاب، واعتمد الأنموذج على البيانات الشهرية لدرجة حرارة الهواء والرطوبة النسبية في محطة طرطوس، كما استُخدِمت بيانات التبخر الشهري من حوض التبخر الأميركي صنف A لغرض التحقق من صحة أداء الشبكة، بعد تعديل نتائجها باستخدام تقانة Simulink المتاحة في حزمة برمجيات الماتلاب. أثبتت نتائج الدراسة أنَّ الشبكة العصبية الصنعيَّة متعددة الطبقات، وذات الانتشار العكسي للخطأ تعطي نتائج جيدة في تقويم التبخر– نتح المرجعي الشهري، اعتماداً على مجموعة البيانات المستخدَمة. Evapotranspiration forms one of the elements of the hydrological cycle that is hard to measure its actual amounts in field conditions. So it is estimated in terms of calculations of experimental relations depending on climatic elements data. These estimations include different errors because of approximation processes. This research aims to calculate an estimation of the monthly reference evapotranspiration amount in Tartous (on the east coast of the Mediterranean Sea), depending on the technique of Artificial Neural Network (ANN); the mathematical model is built by the (NN-tool box), which is one of the Matlab tools, based on monthly air temperature and relative humidity data taken from Tartous meteorological station. The data of monthly pan evaporation (Class A pan) has been used after modifying its results for the purpose of checking the performance accuracy of the network, using Simulink techniques of Matlab Programs Package. The results of the research verify that a multi-layer ANN of error back-propagation algorithm gives good results in estimating monthly reference evapo-transpiration for the data used.